2020
DOI: 10.1038/s41598-020-74709-2
|View full text |Cite
|
Sign up to set email alerts
|

Towards programmable friction: control of lubrication with ionic liquid mixtures by automated electrical regulation

Abstract: For mechanical systems in relative motion it would be fascinating if a non-mechanical stimulus could be used to directly control friction conditions. Therefore, different combinations of lubricants and external triggers for tribological influence have already been investigated. We show that when two metallic friction partners are lubricated with ionic liquid mixtures (ILM), consisting of long-chain cation and two different high charge/mass ratio anion containing ILs, the application of an electric impulse indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…[47] Using external electrical control, Gatti et al proposed the concept of programmable control of friction, which could control the adsorption, exchange, and orientation of multicomponent ILs on a surface by changing the polarization of charged friction surfaces using a compiled program, to change the coefficient of friction to a greater extent more accurately and faster. [48] Although ILs seem to be a suitable and smart alternative to conventional lubricants, their current high manufacturing costs make their direct application as lubricants impractical. In addition, current studies focus more on the lubrication mechanism of ILs, although some studies have reported on the lubrication conditions of pure ILs under the influence of electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…[47] Using external electrical control, Gatti et al proposed the concept of programmable control of friction, which could control the adsorption, exchange, and orientation of multicomponent ILs on a surface by changing the polarization of charged friction surfaces using a compiled program, to change the coefficient of friction to a greater extent more accurately and faster. [48] Although ILs seem to be a suitable and smart alternative to conventional lubricants, their current high manufacturing costs make their direct application as lubricants impractical. In addition, current studies focus more on the lubrication mechanism of ILs, although some studies have reported on the lubrication conditions of pure ILs under the influence of electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…The changing technological landscape, with the rapid shift towards vehicle electrification and green energy production being the obvious examples, along with environmental concerns, has resulted in a need for lubricants with enhanced functionality such as electrical responsivity 11 14 . It is the role of chemists to facilitate the tribological advances by developing new formulations, sometimes even with new molecules, in an attempt to feed the industrial and societal demands.…”
Section: Introductionmentioning
confidence: 99%
“…10 The changing technological landscape, with the rapid shift towards vehicle electri cation and green energy production being the obvious examples, along with environmental concerns, has resulted in a need for lubricants with enhanced functionality such as electrical responsivity. [11][12][13][14] It is the role of chemists to facilitate the tribological advances by developing new formulations, sometimes even with new molecules, in an attempt to feed the industrial and societal demands.…”
Section: Introductionmentioning
confidence: 99%